Mechanical and Microstructural Evaluation of DMAG Welding of Structural Steel - Mert, Tolga; Gultekin, Nurullah; Karaaslan, Ahmet (SAGE PUBLICATIONS LTD, 2015)
Double channel torch, which allows concentric flow of two different shielding gases, was designed and manufactured in order to pursue double channel torch gas metal arc welding of unalloyed structural steel S235JR (EN 10025-2) with fourteen passes. Tensile and Charpy V-notch tests were realized and the results were compared with those of conventional gas metal arc welding. In order to evaluate mechanical testing results, microstructural analyses were conducted. It was found that the increase with double channel gas metal arc welding process in yield and tensile strengths as well as in toughness tests, especially in subzero temperatures, compared with conventional gas metal arc welding was due to longer columnar grains and finer tempered zone grain structure between passes and due to solidification and less dendritic structure formation in all-weld metal in double channel gas metal arc welding.
Keywords: SHIELDING GASES; STAINLESS-STEEL; Thermodynamics; Engineering